2011
DOI: 10.1073/pnas.1017137108
|View full text |Cite
|
Sign up to set email alerts
|

Gain of chromosome band 7q11 in papillary thyroid carcinomas of young patients is associated with exposure to low-dose irradiation

Abstract: The main consequence of the Chernobyl accident has been an increase in papillary thyroid carcinomas (PTCs) in those exposed to radioactive fallout as young children. Our aim was to identify genomic alterations that are associated with exposure to radiation. We used array comparative genomic hybridization to analyze a main (n = 52) and a validation cohort (n = 28) of PTC from patients aged <25 y at operation and matched for age at diagnosis and residency. Both cohorts consisted of patients exposed and not expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 53 publications
5
67
3
2
Order By: Relevance
“…They have joined the discovery cohort Genrisk-T with validation cohorts Genrisk-T plus and UkrAm (CTB tumors only) which were investigated in earlier exploratory studies related to the CLIP2 marker (14,15). All PTC cases are listed in Table.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have joined the discovery cohort Genrisk-T with validation cohorts Genrisk-T plus and UkrAm (CTB tumors only) which were investigated in earlier exploratory studies related to the CLIP2 marker (14,15). All PTC cases are listed in Table.…”
Section: Methodsmentioning
confidence: 99%
“…The histological composition of more than 90% of all thyroid carcinoma from the Chernobyl studies pertains to papillary thyroid cancers (PTC). Genomic analysis of PTC samples stored in the Chernobyl tissue bank (CTB, ) revealed a DNA copy number gain on chromosome band 7q11.23 and mRNA overexpression of the CLIP2 gene related to radiation exposure (14). The samples came from the Genrisk-T cohort of patients which were exposed at very young age below 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…However whether radiation induced tumours have a specific mutation profile remains to be established. As noted in Section 4.3.2, a recent study has identified a potential genetic signature of radiationinduced thyroid tumours [148]. In another study assessing the mutational pattern of a reporter gene in mouse fibroblasts upon fractionated IR exposure, a high proportion of T:A !…”
Section: Biomarkers Related To Induced Mutationsmentioning
confidence: 98%
“…For example IQGAP1 CNA is associated with the invasiveness of thyroid cancer and may represent a novel prognostic marker and therapeutic target for this cancer [147]. In addition, a study conducted on young patients with papillary thyroid carcinoma exposed to an estimated average dose of 150 mGy after the Chernobyl accident showed an amplification of the region 7q11.22-11.23 in a subgroup of exposed patients, and could potentially represent a biomarker of exposure, although possibly limited to certain cases or dose ranges [148]. However whether the presence of specific CNAs reflects the tumour aetiology remains to be examined.…”
Section: Copy Number Variants (Cnv) and Alterations (Cna)mentioning
confidence: 99%
“…Similarly, the greatest increase in the rate after irradiation was found for RET/PTC1 (Ushenkova et al 2015), exposure-specific gain of 7q11, and overexpression of the CLIP2 gene (Hess et al 2011).…”
Section: Association Between Genome Damage Birth Anomalies and Cancmentioning
confidence: 93%